2021
DOI: 10.1111/1475-6773.13631
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urgent care centers on nonemergent emergency department visits

Abstract: Objective: To estimate the impact of urgent care centers on emergency department (ED) use. Data Sources: Secondary data from a novel urgent care center database, linked to the Healthcare Cost and Utilization Project State Emergency Department Databases (SEDD) from six states. Study Design: We used a difference-in-differences design to examine ZIP code-level changes in the acuity mix of emergency department visits when local urgent care centers were open versus closed. ZIP codes with no urgent care centers serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Yet, this service acts only on an ‘afterhours’ basis; operationalisation as an urgent care centre geared towards PAT presentation characteristics (early ED shift and lower priority) with patients streamed to this service based on triage recommendations could be beneficial for addressing non‐urgent presentations. Current urgent care centres have demonstrated success internationally, reducing costly non emergent ED visits and increasing access to timely healthcare for patients 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, this service acts only on an ‘afterhours’ basis; operationalisation as an urgent care centre geared towards PAT presentation characteristics (early ED shift and lower priority) with patients streamed to this service based on triage recommendations could be beneficial for addressing non‐urgent presentations. Current urgent care centres have demonstrated success internationally, reducing costly non emergent ED visits and increasing access to timely healthcare for patients 26 …”
Section: Discussionmentioning
confidence: 99%
“…Current urgent care centres have demonstrated success internationally, reducing costly non emergent ED visits and increasing access to timely healthcare for patients. 26…”
Section: Discussionmentioning
confidence: 99%
“… 15 A study of six American states demonstrated a 17.2% reduction in ED visits during times when UCCs in the corresponding zip code were open. 11 Similarly, areas within the United States with high UCC use have been found to correspond with lower ED use. 16 However, a review of British efforts to increase urgent care availability suggests that individuals do not generally substitute newly established, more appropriate care avenues for older ones, including ED use.…”
Section: Resultsmentioning
confidence: 96%
“… 9 Lower-acuity care adequacy for many ED presentations is well-established, with up to half manageable outside the ED. 10 , 11 Patients seeking care from general practitioner after-hours services have been found to more often be older, female, and presenting with non-injury concerns compared to ED presentations, suggesting that patients do discriminate when selecting services. 10 However, reduced ED demand is inconsistent among alternative care models.…”
Section: Resultsmentioning
confidence: 99%
“…Studies like these show the positive impact that educating the public about the healthcare system can have on ED utilization [26]. Furthermore, increasing numbers of urgent care clinics can also serve to treat patients with non-emergent conditions [27].…”
Section: Discussionmentioning
confidence: 99%